DUE DILIGENCE AND RISK MITIGATION FOR WINNERS OF COLLATERAL LAND AUCTIONS - Suwito, Suwito; Sulani, Sulani; Khayru, Rafadi Khan; Putra, Arif Rahman; Darmawan, Didit (Gapenas Publisher, 2025)
This study aims to analyze the legal protection afforded to recipients of land rights acquired through execution auctions involving fiduciary security and mortgage rights, focusing on the identification of legal gaps, substantive risks, and the construction of a due diligence mechanism. The method employed is normative legal research utilizing legislative, jurisprudential, and doctrinal approaches. The results indicate that the legal protection for auction winners possesses a strong normative basis within the Mortgage Rights Law and the Fiduciary Security Law, reinforced by Supreme Court jurisprudence that protects auction winners acting in good faith. However, the primary legal gap lies in the imperfection of the land registration system, the existence of unrecorded third-party rights, and vulnerability to procedural defects in the auction. Substantive risks faced by auction winners include ownership disputes, claims from heirs, the presence of physical occupants, as well as uncertainty regarding spatial planning status and tax liabilities. To mitigate these risks, the study formulates an effective due diligence framework encompassing verification of certificate legality, physical and social field inspections, tracing of encumbrances from agreements, and confirmation of spatial compliance. It is concluded that auction winners must transition from reliance on passive legal protection towards an active approach through comprehensive due diligence, while regulators need to enhance transparency regarding auction object information.